2020
DOI: 10.3329/bjz.v48i1.47881
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Parasites of Captive Asiatic Black Bear in Three Zoological Parks of Bangladesh

Abstract: Forty-two freshly defecated fecal samples from captive Asiatic Black Bear (Ursus thibetanus) were collected between May 2017 and April 2018 from Bangladesh National Zoo, Dhaka, Shaheed A.H.M. Central Park and Zoo, Rajshahi and Bangabandhu Sheikh Mujib Safari Park, Gazipur. The collected samples were processed by Formol-ether concentration technique. Altogether nine different gastrointestinal (GI) parasites were observed and identified, which include one protozoan, Coccidia spp. (42.86%); four cestodes, Hymenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Our data are supported by Partridge (1992) and Moran et al (1994), who reported that young and immature bears were more susceptible to infection than were adult bears. Similar findings were found in grizzly bears (Ursus arctos) in Montana and Wyoming (Worley et al 1976), black bear (U. americanus) cubs in Florida (Foster et al 2004), Asiatic black bears in zoological parks in Bangladesh (Liza et al 2020) Ancylostoma spp. has the highest prevalence of all parasites that infected the captive sun bears in Malaysia in our study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our data are supported by Partridge (1992) and Moran et al (1994), who reported that young and immature bears were more susceptible to infection than were adult bears. Similar findings were found in grizzly bears (Ursus arctos) in Montana and Wyoming (Worley et al 1976), black bear (U. americanus) cubs in Florida (Foster et al 2004), Asiatic black bears in zoological parks in Bangladesh (Liza et al 2020) Ancylostoma spp. has the highest prevalence of all parasites that infected the captive sun bears in Malaysia in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Our data are supported by Partridge (1992) and Moran et al (1994), who reported that young and immature bears were more susceptible to infection than were adult bears. Similar findings were found in grizzly bears ( Ursus arctos ) in Montana and Wyoming (Worley et al 1976), black bear ( U. americanus ) cubs in Florida (Foster et al 2004), Asiatic black bears in zoological parks in Bangladesh (Liza et al 2020), and Eurasian brown bear ( U. arctos arctos ) in the East Carpathians Biosphere Reserve of Slovakia (Molnár et al 2020). On the other hand, studies on other mammals such as lions ( Panthera leo ; Sulehria et al 2014), white-tailed deer ( Odocoileus virginianus ; Grear et al 2006), African buffalo ( Syncerus caffer ; Jolles et al 2005), and wood bison ( Bison bison ; Joly and Messier 2004) reported more parasite prevalence in adults than juveniles possibly because these animals, like lions, are territorial and adult males protect their territory from invaders.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation